Intestinal Pathogenic Escherichia coli: Insights for Vaccine Development - Rojas-Lopez, Maricarmen; Monteiro, Ricardo; Pizza, Mariagrazia; Desvaux, Mickaël; Rosini, Roberto (Frontiers in Microbiology, 2018)
Diarrheal diseases are one of the major causes of mortality among children under five years old and intestinal pathogenic Escherichia coli (InPEC) plays a role as one of the large causative groups of these infections worldwide. InPECs contribute significantly to the burden of intestinal diseases, which are a critical issue in low- and middle-income countries (Asia, Africa and Latin America). Intestinal pathotypes such as enteropathogenic E. coli (EPEC) and enterotoxigenic E. coli (ETEC) are mainly endemic in developing countries, while ETEC strains are the major cause of diarrhea in travelers to these countries. On the other hand, enterohemorrhagic E. coli (EHEC) are the cause of large outbreaks around the world, mainly affecting developed countries and responsible for not only diarrheal disease but also severe clinical complications like hemorrhagic colitis and hemolytic uremic syndrome (HUS). Overall, the emergence of antibiotic resistant strains, the annual cost increase in the health care system, the high incidence of traveler diarrhea and the increased number of HUS episodes have raised the need for effective preventive treatments. Although the use of antibiotics is still important in treating such infections, non-antibiotic strategies are either a crucial option to limit the increase in antibiotic resistant strains or absolutely necessary for diseases such as those caused by EHEC infections, for which antibiotic therapies are not recommended. Among non-antibiotic therapies, vaccine development is a strategy of choice but, to date, there is no effective licensed vaccine against InPEC infections. For several years, there has been a sustained effort to identify efficacious vaccine candidates able to reduce the burden of diarrheal disease. The aim of this review is to summarize recent milestones and insights in vaccine development against InPECs.